Zemljevid Ilirskih provinc iz leta 1812 = Carte des Provinces illyriennes de 1812 - Orožen Adamič, Milan; Gašperič, Primož; Šumrada, Janez (ZRC SAZU, Založba ZRC, 2012)
In the early 19th century part of the Slovenian, Italian, Austrian, Croatian and Montenegro territory has been included into political and administrative unit known as the Illyrian Provinces. The Illyrian Provinces incurred at the request of Napoleon Bonaparte and, together with its fall also ceased to exist. The edition of this book was prepared in order to celebrate the two hundredth anniversary of the Illyrian Provinces, to highlight the role of cartography in the Slovenia and to emphasize the importance of the historical moment of the causes and consequences of the Illyrian Provinces. Almost unknown Gaetano Palma is the author of cartographic display of the territory of the Illyrian Provinces. The merits of the map are: relatively large map scale, quality cartographic representation of the terrain and systematic breakdown of some cartographic elements. This depiction of the Illyrian Provinces was designed for completely common purpose, which should help to better recognize and to assimilate displayed area. Therefore, the authors have added several important aspects to the reproduction of this map. These are: an overview of the status of a state of the Illyrian Provinces, transparent outline of the main achievements of the Napoleonic Cartography in the Eastern Adriatic and the Eastern Alps regions and detailed geographical description and index of geographical names. Herewith they presented the map and the happening of that time to the modern reader.